Opahcyber-online / Suhada Ahmad - Suhada , Ahmad (2002)
Traditional Petua is an important traditional heritage. There are so many traditional petua that has been inherited for centuries. It has been passed by many styles included oral presentation, presentation by reading and currently, presentation using new technology, web-based. This OpahCyber-Online system has been developed based on several main objectives. First, this system is developed to store up as many petua as possible. Secondly, the system wishes to attract internet users to know more about traditional petua and last but not least, hopefully this system will become a reference centre for traditional petua. This system using on-line application to ensure that the newest information will be delivered to users. Furthermore, it will encourage interactive involvement among users. OpahCyber-Online has been developed using several types of software like Active Server Pages, Personal Web Server, Microsoft Access, Macromedia Firework and Macromedia Flash for better performance. Other than to fulfill users' needs and requirements, hopefully this system will give contribution to new technology in information technology era. Expectedly, this system will improve all the weakness of all available homepage and make sure that traditional petua will not be forgotten by our Malaysian nation in all range of age, especially by the next generation.